Pengembangan Desa Wisata Berbasis Pemberdayaan Sosial di Desa Pejambon Kecamatan Sumberrejo Kabupaten Bojonegoro - Versanudin Hekmatyar (UIN Siber Syekh Nurjati Cirebon, 2021)
The objective of this study is describing tourism village development based on social empowerment. By using qualitative approach, data was collected and presented descriptively. This study assumes that the development of the tourism sector can provide income potential to families in the village and complement each other with agriculture sector. Tourism is a sector that has experienced rapid growth over the last few decades while contributing to poverty reduction in rural areas. The tourism sector is considered as a potential means for socio-economic development and regeneration of rural areas. This study seeks to contributes an understanding of the tourism village development strategy formulated and implemented. The results are as follows social empowerment is a required for developing a sustainable tourism sector. Based on that thing, tourism village development strategy must consider several factors, including; participatory tourism planning, capacity building and empowerment, also the usefulness of rural tourism for the community.